2005
DOI: 10.1086/444440
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Evolution ofPseudomonas fluorescensin Simple and Complex Environments

Abstract: In complex environments that contain several substitutable resources, lineages may become specialized to consume only one or a few of them. Here we investigate the importance of environmental complexity in determining the evolution of niche width over approximately 900 generations in a chemically defined experimental system. We propagated 120 replicate lines of the bacterium Pseudomonas fluorescens in environments of different complexity by using between one and eight carbon substrates in each environment. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
111
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 59 publications
8
111
1
Order By: Relevance
“…The most likely cause of this discrepancy is that in these experiments E. coli was cultured in rich LB medium or glucose, environments in which the ancestor would have a nearly optimal phenotype. In contrast, the ancestral strain of Pseudomonas used in our experiment has very poor growth in carbonlimited serine environments (Barrett et al 2005). Bull et al (2000) found beneficial mutations of large effect (SZ0.8-13.9) when they selected a bacteriophage at very high temperatures, but they did not collect enough mutants to determine the distribution of selection coefficients.…”
Section: Mutations Of Pseudomonas Fluorescens R D H Barrett and Otmentioning
confidence: 74%
“…The most likely cause of this discrepancy is that in these experiments E. coli was cultured in rich LB medium or glucose, environments in which the ancestor would have a nearly optimal phenotype. In contrast, the ancestral strain of Pseudomonas used in our experiment has very poor growth in carbonlimited serine environments (Barrett et al 2005). Bull et al (2000) found beneficial mutations of large effect (SZ0.8-13.9) when they selected a bacteriophage at very high temperatures, but they did not collect enough mutants to determine the distribution of selection coefficients.…”
Section: Mutations Of Pseudomonas Fluorescens R D H Barrett and Otmentioning
confidence: 74%
“…When they were reared on low food rations, these differences in growth rate disappeared. Analogous interactions between resource quality and fitness were observed in selection experiments on Pseudomonas fluorescens in which selected lines were reared over multiple generations on different nutrient concentrations (14). These selection experiments are important because they clearly demonstrate that resource availability can shape how organisms evolve, and the examination of interactions between multiple food treatments and fitness best illuminates the responses to resource-based selection.…”
mentioning
confidence: 79%
“…An effective way to reveal the influence of resource availability on evolutionary change is to measure interactions between food levels and fitness (12)(13)(14). Falconer and Latyszewski (12) selected for increased growth rates in mice reared at either high or low levels of food availability.…”
mentioning
confidence: 99%
“…Experimental evolution has thus enabled the study of the adaptation of bacteria to the conditions posed by structured versus unstructured habitats (10,11,12,13). The majority of the experiments have used simple limiting/selective conditions (limiting substrates), and only a few studies have included more complex conditions (14), for instance, growth under fluctuations in temperature (15), pH (16), or with combined limited resources (17). As we currently ignore how bacteria may adapt to prolonged growth in complex media, there is a need for studies that address this question (18), which is of major importance to address the effects of the putative coexistence of differentially evolved forms.…”
mentioning
confidence: 99%